Biodiversity of Trichoderma spp. in TUB culture collection - Szakacs G (浙江大学学报. 农业与生命科学版)
Culture collection of the Technical University of Budapest (TUB) comprises approx. 2800 microorganisms with special emphasis on lignocellulose degrading fungi and actinomycetes. For isolation and screening programs, 460 soils are stored at+5 ℃.They were collected in 58 countries, including extreme environments.There are 860 Trichoderma strains in TUB collection, representing 45 countries and 173 soils and/or tree barks as isolation sources. Trichoderma spp. selected from soils in the tundra region (Rocky Mountains, Colorado) grow at low temperatures such as 5-10 ℃. These strains practically do not grow at 30 ℃. On the contrary, many Trichoderma strains were isolated from tropical or subtropical soils and decaying plant materials at 35-40 ℃ in Brazil, Peru, Costa Rica, Guatemala, Hawaii, Tanzania, Thailand and Indonesia. Trichoderma strains tolerating limited oxygen supply were selected from river muds and sediments. Trichoderma spp. tolerating or partially degrading 2,4-dichlorophenol and 2,4, 6-trichlorophenol in 20 mg/kg concentration were selected from polluted soils.As a part of an attempt to assess the global biodiversity of Trichoderma, researchers of Technical University of Vienna and Agriculture Canada, in collaboration with TUB collection, identified and characterized seven new assumed taxa of Trichoderma from Eurasia.